Ksiądz Józef Dobrochowski (1904-1988) jako informator UB o pseudonimie „Grzmot” (Kronika Bydgoska, 2014)
The Bydgoszcz Parish of the Polish Catholic Church was reactivated after World War II by Fr. Józef Dobrochowski (1904-1988). He also was working as a UB informer AKA “Thunder”. He not only informed on his parishioners, but also performed tasks for the secret service in the Church, including removal of Bishop Józef Padewski, who died in prison in 1951. As the chairman of the PNKK Temporary Government College he set his colleague priests at variance and embezzled funds, as a result of which he was withdrawn from the Church management. He established relations with the mentally ill bishop vagabond Ignacy Wysoczański. “Thunder’s ” insubordination as a secret agent led to UB’s withdrawal from all religious activities in 1952. In that time, the authorities started to treat the Polish Catholic Church as a bothersome religious organization of low importance, in particular with the fight against the Roman Catholic Church. They supported sabotage in the form of patriotic priests and Caritas.